Comparison and Performance Analysis of Bio-Diesel Fuel and Mustard Oil Blends in Single Cylinder Diesel Engine - T.Thirumalai, Dr.; T.Siva kumar, Dr.; Harsha Vardhan Reddy, A (International Journal of Engineering and Technology, 2018)
Present day advancement  is much subject to fossil essentialness and imperativeness got from fossil resources is significantly higher than various assets. Biodiesel, a promising elective fuel has expanded tremendous thought due to the foreseen shortness of standard forces. The usage of fluid energizes like biodiesel delivered from mustard oil by transesterification process speaks to a standout amongst the most encouraging alternatives as exchange to regular  diesel and petroleum products. In this paper, the oil is changed over into butyl ester known as biodiesel. Biodiesel oil and diesel were mixed in the proportion of 10:90 and 20:80  in the presence of homogeneous acid catalyst.. The physical properties, for example, density, kinematic, viscosity, flash point fire point were resolved for mustard oil, and mustard butyl ester. Similar qualities  was carried out for the diesel as a fuel to get the information for investigation. Diesel and its mixtures  of mustard oils were tested in a CI Engine for execution and emission discharge qualities which demonstrated extensive enhancement in improvement in reducing the emission of  gases.